Perlindungan Konsumen Korban Transaksi Pay Later Traveloka (Contoh Kasus Trias Dian Lestari) - Mulyadi Mulyadi; Gunawan Djajaputra (Syntax Corporation, 2023)
Economic development as part of the concept of national development, as an effort to realize the welfare of the people who are just and prosperous. In order to strengthen national development, the government invites the banking world to participate in collecting and distributing public funds, both on a small and large scale. The government issued basic rules of banking law, namely Law Number 10 of 1998 concerning Banking (which was later shortened to the Banking Law). The aim is to regulate various banking activities, both transactions, depositing money, investment and credit so that the public also gets legal protection. Implementation of financial business services to connect lenders with loan recipients to reach loan agreements in rupiah directly through digital platforms using internet services. PayLater is a technology-based lending and borrowing service with the motto